Differences in CXCR4 expression between day 5 and day 6 euploid blastocysts: A predictor of implantation potential in single embryo transfer - Chularat Suwandee; Paweena Thuwanut; Chanakarn Suebthawinkul; Punkavee Tuntiviriyapun (Clinical and Experimental Reproductive Medicine, 2026)
Objective: This study aimed to compare the expression of implantation-related genes in trophectoderm cells between normally developing (day 5) and delayed (day 6) euploid blastocysts.Methods: Trophectoderm biopsies were performed on blastocysts at either day 5 or day 6 of development. Preimplantation genetic testing for aneuploidy was conducted using next-generation sequencing. The expression levels of GAPDH, CXCR4, CXCL12, HSD3B1, HSD17B1, ITGAV, LAMA1, and MUC15 were measured from the remaining trophectoderm samples of euploid blastocysts using real-time quantitative polymerase chain reaction. Differences in gene expression levels between day 5 and day 6 euploid blastocysts were analyzed with the 2-ΔΔCt method. Pregnancy outcomes were assessed following single embryo transfer.Results: Euploid blastocysts from day 5 (n=10) and day 6 (n=10) were included in the analysis. The expression level of CXCR4 was significantly lower in day 5 blastocysts compared to day 6 blastocysts (p=0.031). CXCL12, HSD17B1, ITGAV, and LAMA1 exhibited upregulated expression, while HSD3B1 and MUC15 showed downregulation in both day 5 and day 6 blastocysts, without significant differences between groups. Although gene expression did not differ significantly between pregnant and non-pregnant groups, early upregulation of CXCR4 was observed in the non-pregnant group following day 5 embryo transfer.Conclusion: As the only gene associated with implantation, CXCR4 displayed a distinctive expression profile that increased during blastocyst development. Aberrant CXCR4 expression at specific stages of blastocyst development may influence pregnancy outcomes.